TEORI BELAJAR ROBERT MILLS GAGNE DAN PENERAPAN DALAM PEMBELAJARAN MATEMATIKA - Destika Tarihoran; Mhd. Nau Ritonga; Roslian Lubis (JURNAL MathEdu (Mathematic Education Journal), 2021)
ABSTRACT This study aims to describe of the learning theory of Robert Mills Gagne and the applying in learning mathematics on the students in Pananggahan Village. The research was conducted by applying descriptive qualitative. Instrument of the research included questionnaire (Guttman scale) and documentation. The respondents of the research consist of 30 students. The result of the research shows 1) the learning theory of Robert Mills Gagne is the process of changing one's behavior as a result of processing new information with previous experiences and 2) The applying the learning theory of Robert Mills Gagne in learning mathematics at the students of Pananggahan Village in Covid -19 pandemic haves troubles because students’ lack of concentration in doing the assignments given by the teacher, students feel bored with learning mathematics online, students do not understand the material presented by the teacher online, there are too many assignments given by the teacher, and many students do not have electronic facilities.